Correct design of vertical borehole heat exchanger systems through the improvement of the ASHRAE method. (3rd October 2017) - Fossa, Marco
Abstract : In this article, the ASHRAE method for borehole heat exchanger field design is deeply discussed in order to trace its theory and physical meaning. The aim of the article is corroborate previous studies in order to demonstrate that the current version of the method is not suitable for a reliable sizing of the borehole field since the criteria for calculating the temperature penalty term fail to large extent from a correct estimation. Based on the above findings (demonstrated by a comprehensive comparison with reference results pertaining a vast number of borefield configurations), a new version of the temperature penalty calculation procedure is presented that is able to maintain the ASHRAE formalism and simplicity while enhancing the accuracy of the design results.